Analysis of commercially available snake antivenoms reveals high contents of endotoxins in some products - Solano Blanco, Gabriela (2024)
As injectable therapeutics, snake antivenoms must meet specifications for endotoxin content. The Limulus amebocyte lysate (LAL) test was used to evaluate the endotoxin content in several commercially available antivenoms released for clinical use. It was found that some products have endotoxin concentrations higher than the accepted limit for these contaminants. These results emphasize the need to include endotoxin determination as part of the routine evaluation of antivenoms by manufacturers and regulatory agencies.